MODELING OF POLLUTION LOAD CAPACITY AND ASSIMILATIVE CAPACITY USING WASP MODEL (A CASE STUDY: DOWNSTREAM LANDAK RIVER) - Chika Ayu Anggraeni, Annisa
The Landak River is one of the tributaries of the Kapuas River in the coastal area of West Kalimantan Province which crosses three regencies/cities namely Landak Regency, Kubu Raya Regency and Pontianak City which are used as raw water facilities. In terms of quantity, the availability of raw water but abundant from the quality of the raw water sources has been polluted. Based on monthly monitoring data released by BWSK I, the overall water quality of the Landak River is in the low range upstream and slightly shifted to polluted downstream based on the pollutant index. Therefore, a study was conducted to analyze the results of the existing air quality conditions in 11 segments of the downstream Landak River based on the parameters BOD, COD, DO, TSS, Nitrate and predict changes in water quality from point source and non-point sources along the river with the software Water Analysis Simulation Program (WASP). In addition, analysis of the assimilation capacity of water bodies in receiving pollutant loads. The results showed that point sources contributed the highest pollution load (87%) compared to non-point sources (13%). Based on the analysis of existing conditions and water quality status, the downstream Landak River is categorized as lightly polluted with a pollution index value (IP) of 1.44. The pollutant load capacity that is allowed to enter the Landak River is obtained from the simulation results of the WASP model with BOD parameters of 152.159 kg/day and 1.003.768 kg/day for COD. So from the results of assimilation capacity, it is found that the waters of the downstream Landak River have exceeded the assimilation capacity limit or have overcapacity in accommodating the pollutant load. Thus, additional air control controls are needed to control and reduce pollution in the downstream Landak sub-watershed.